2019
DOI: 10.3390/ijms20235864
|View full text |Cite
|
Sign up to set email alerts
|

microRNAs Regulating Human and Mouse Naïve Pluripotency

Abstract: microRNAs are ~22bp nucleotide non-coding RNAs that play important roles in the post-transcriptional regulation of gene expression. Many studies have established that microRNAs are important for cell fate choices, including the naïve to primed pluripotency state transitions, and their intermediate state, the developmentally suspended diapause state in early development. However, the full extent of microRNAs associated with these stage transitions in human and mouse remain under-explored. By meta-analysis of mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 89 publications
(131 reference statements)
1
20
1
Order By: Relevance
“…Specifically, microRNA target genes showed more enrichment in stress response, hypoxia, and hormone response pathways, which is consistent with the diapause phenotype. Inversely, target genes down-regulated in diapause (their microRNAs being up-regulated in diapause) showed enrichment in cellular morphogenesis, differentiation, and development, which is consistent with diapause as a suspended developmental stage [3].…”
Section: Looking For New Players Involved In Embryonic Diapausesupporting
confidence: 65%
See 1 more Smart Citation
“…Specifically, microRNA target genes showed more enrichment in stress response, hypoxia, and hormone response pathways, which is consistent with the diapause phenotype. Inversely, target genes down-regulated in diapause (their microRNAs being up-regulated in diapause) showed enrichment in cellular morphogenesis, differentiation, and development, which is consistent with diapause as a suspended developmental stage [3].…”
Section: Looking For New Players Involved In Embryonic Diapausesupporting
confidence: 65%
“…More micro-RNA explorations Micro-RNAs regulate gene expression in different physiological systems. While micro-RNAs of the Let-7 family have been previously shown to be potentially regulating diapause, additional microRNA regulators of diapause and their target genes still remain to be explored [3]. Interestingly, consistent connections between 38 microRNA and 274 target genes were identified for up or down regulations in the mouse model.…”
Section: Looking For New Players Involved In Embryonic Diapausementioning
confidence: 98%
“…MicroRNAs can be expressed in cell- and developmental-specific manners [ 110 ]. A recent meta-analysis evaluating data obtained from microRNA-seq, RNA-seq and metabolomics datasets from mouse and human ESCs revealed that 115 miRNAs show a differential expression profile during the naïve-to-primed transition [ 111 ]. These miRNAs act by repressing the developmental SONIC HEDGEHOG (SHH) pathway in the naïve state and regulating metabolic pathways such as oxidative phosphorylation, fatty acid metabolism and amino acid transport during the transition.…”
Section: Naïve To Primed Pluripotency Transition: the Crucial Rolementioning
confidence: 99%
“…MicroRNAs, a class of single-stranded non-coding RNA, are widespread in various organisms, regulate gene expression at post-transcriptional level [1][2][3][4] , and also play important roles in inflammation, tumorigenesis and progression [5][6][7] . MicroRNA-155 is located on chromosome 21q21 and aberrantly expressed in a variety of solid tumors.…”
Section: Introductionmentioning
confidence: 99%